Patient Satisfaction About Hospital Services: A Study from The Outpatient Department of Tertiary Care Hospital, Jabalpur, Madhya Pradesh, India - Sharma, Arvind; Kasar, P K; Sharma, Richa (National Journal of Community Medicine, 2014)
Background: Patient satisfaction is an important means of measuring the effectiveness of health care delivery and quality of medical care. It denotes the extent to which general health care needs of the patient are met to their requirements. The most important reason to conduct patient satisfaction surveys is that they provide the ability to identify and resolve potential problems before they become serious. This study was designed to assess the patient satisfaction regarding the services provided in out-patient department. Material and Methods: A cross-sectional study was carried out in 100 randomly selected patients. They were interviewed at the exit point of outpatient department during the period from 21/09/2013 to 25/09/13. The data were collected on predesigned and pretested questionnaire. Results: Most of the respondents were satisfied with availability of services, professional care, waiting time, behavior of consultant, nurses, paramedical staff and other staff. The overall satisfaction level was 73% excellent to good, 22% average and 94% respondents answered ‘yes’ to the question - ‘would you recommend this hospital to friends and family’. Out of total 68% respondents were unsatisfied with toilet facility and 56% were unsatisfied with drinking water facility. Conclusion: OPD services in a hospital need to be improved by developing patient feedback system.